Efektivitas Tagetes spp. sebagai tanaman antagonis untuk mengendalikan nematoda puru akar pada tanaman Seledri (Apium graviolens L.) - Wabdaron, Victoria; Ruimassa, Reymas M. R.; Martanto, Eko Agus (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: Celery is an agricultural crop that has long been cultivated by indigenous Papuan people who live in the Arfak Mountains Regency because the soil structure and climate are suitable for growing celery. Currently, Arfak Mountains Regency is an area that fulfills the celery needs of Manokwari Regency so that celery plants become a source of income for local residents. One of the cultivation problems experienced by farmers is nematode disorders which cause celery to not grow to its genetic potential and even die. This is known by the presence of a kind of knot on the roots which causes abnormal growth in celery. Therefore, the aim of this research is to identify the nematodes that cause root knots and control them biologically using 2 natural control agents for Marigold plants, namely Tagetes erecta and T. patula. This plant produces yellow and red flowers and has a strong odor. The method used is a descriptive method with observation techniques. Data analysis was carried out using the Spearman Correlation test which was narrated with the help of tables and pictures. The research results showed that root knots were identified as being caused by 3 nematode species, namely Meloidogyne javanica, M. incognita, and M. arenaria. The differences between the three nematode species are known through identification of the vulva morphology found in each species. The research results also show that both Marigold species produce 2 types of secondary metabolite compounds, namely phenols and flavonoids, which function to trap and control the population and spread of nematodes. The presence of marigold plants causes celery to achieve maximum growth, number of branches and wet stover weight in suitable with its genetic potential.